FACTORS AFFECTING MALAY SPEAKING ANXIETY AMONG BACHELOR OF ARTS (MALAY LANGUAGE) STUDENTS, YALA RAJABHAT UNIVERSITY - Sadama, Nurhuda (Journal of MCU Nakhondhat, 2022)
The objectives of this research were 1) to study the factor levels affecting Malay speaking anxiety among Malay-language students, 2) to examine the anxiety level of Malay speaking, 3) to investigate the factors affecting Malay speaking anxiety, and 4) to propose the guidelines of anxiety reduction of Malay speaking. This research was conducted with mix-method where the population is of 132 Malay-language students of Yala Rajabhat University. The research instrument was a five-Linkert scale questionnaire while the data was analyzed by using percentage statistics, Arithmetic Mean, Standard Deviation, and Multiple Regressions. The results show that teaching behavior of teachers was ranked at the top factor levels, mean 4.42, whereas family aspect came as second factor levels, mean 4.25, affecting Malay speaking anxiety. The level of Malay speaking anxiety among Malay-language students was remarkably high. In addition to that, an analysis of factors affecting Malay speaking anxiety among Malay language students found that teaching behavior of teachers and family were the main factors affecting Malay speaking anxiety at .05 significantly. Lastly, guidelines that students attaching great importance towards adequate and various learning activities of Malay language teaching are recommended.